2024
DOI: 10.1039/d3en00910f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of UV-responsive hydrogels based on nanocellulose and their utilization in fungicide delivery

Chaoqun You,
Xinyue Ji,
Hanchen Lin
et al.

Abstract: Environmental responsive fungicide carrier systems can realize the on-demand intelligent delivery of drugs through different stimulus reactions, improve the utilization rate of fungicides, and effectively prevent and control pests. Nanocellulose...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The growth of most crops depends on light, thus light-response nanopesticides hold great potential for agriculture applications where ample solar radiation can trigger the liberation of AIs encapsulated within these nanopesticides. You et al 85 reported a novel cellulose-based hydrogel (ASB@AZO−CNC) synthesized by cross-linking oxidized cellulose nanocrystals (CNC) with azobenzene (AZO). The photosensitive AZO can inverse the configuration after absorbing energy under specific wavelength ultraviolet light, enabling the controlled release of pesticide from the hydrogel, resulting in a 6.4 times higher release rate compared to nonilluminated conditions.…”
Section: Stimuli-responsive Triggers Of Cellulose-based Nanopesticidesmentioning
confidence: 99%
“…The growth of most crops depends on light, thus light-response nanopesticides hold great potential for agriculture applications where ample solar radiation can trigger the liberation of AIs encapsulated within these nanopesticides. You et al 85 reported a novel cellulose-based hydrogel (ASB@AZO−CNC) synthesized by cross-linking oxidized cellulose nanocrystals (CNC) with azobenzene (AZO). The photosensitive AZO can inverse the configuration after absorbing energy under specific wavelength ultraviolet light, enabling the controlled release of pesticide from the hydrogel, resulting in a 6.4 times higher release rate compared to nonilluminated conditions.…”
Section: Stimuli-responsive Triggers Of Cellulose-based Nanopesticidesmentioning
confidence: 99%
“…Additionally, the development and application of nanocellulose-based materials, particularly hybrid composites that incorporate nanocellulose polymers, have garnered extensive research interest [ 25 , 26 , 27 , 28 , 29 ]. These hybrid composites exhibit unique physical and chemical properties and broad biological functionality due to their natural polymer nanostructure, leading to a wide range of applications [ 30 ] such as personal care products [ 31 ], noble-metal sorption [ 32 ], bone regeneration self-cleaning textile [ 33 ], the food industry [ 34 ], electronics [ 35 , 36 , 37 ], energy harvesting [ 38 ], biomedicine [ 39 , 40 , 41 , 42 ], and environmental protection [ 43 , 44 ]. This underscores the versatile utility of nanocellulose-based materials in advancing sustainable solutions [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%